Behavioral response to tactile stimuli relates to brain response to affective touch in 12-month-old infants - Miguel, Helga O. (2020)
Affective touch activates a brain network responsible for processing social-emotional stimuli in infants, children, and adults, with a core node in the superior temporal sulcus (STS). STS is known to be a region highly susceptible to individual variability, including for tactile stimuli processing. However, little is known about how this region is recruited to process affective touch in infancy. The aim of this study was to examine brain activity to affective touch in the temporal region (STS) and understand if it relates to behavioral patterns of sensory-over responsivity (SOR) to touch. Twelve-month-old infants (n = 24) were given affective and discriminative stimuli to the forearm while they were watching a silent movie. Brain activation was recorded in the STS for measures of oxy-hemoglobin (HbO(2)) and deoxy-hemoglobin (Hbb) using functional near infra-red spectroscopy (fNIRS). Aversive responses to tactile stimuli were measured using the Infant-Toddler Sensory Profile. A significant hemodynamic response increase in HbO(2) to affective touch was observed in the STS for infants with less aversive behavioral responses to tactile stimuli. The findings suggest that brain activity in the STS for affective touch might be related to individual differences in the affective reaction toward touch.